Features of cellular immunity and regeneration for alcoholic fibrosis of the liver - N. D. Gazatova; K. A. Yurova; D. V. Gavrilov; M. A. Vulf; V. V. Novitskii; N. M. Todosenko; L. S. Litvinova (Бюллетень сибирской медицины)
Purpose. The subpopulation composition of peripheral blood lymphocytes was evaluated in patients with alcoholic liver fibrosis (ALF).Materials and methods. The study included 62 patients with ALF; 15 patients abusing alcohol without liver fibrosis and 20 conditionally healthy donors. In samples of lysed peripheral blood, the number of cells bearing surface markers was determined by flow cytometry. In patients with ALF at terminal stages of fibrosis, significant lymphopenia was recorded with a change in the composition of the main subpopulations of lymphocytes relative to the values of conditionally healthy donors and the comparison group.Results. We identified in the blood of ALF patients with terminal (III–IV) stage (relative to control and comparison group) of the relative number of naive (TN) and central memory T-lymphocytes (TCM) associated with an increase in the number of effector cells (TEM and TEMRA) allows us to suggest in this category of patients the direct differentiation of TN and TCM lymphocytes to effector (TEM and TEMRA), which can aggravate the course of the tissue-destructive process due to the high biocidal activity of the latter. Elevated levels of hematopoietic (CD34 and CD133) cells in the peripheral blood at the initial and moderate stages. (I–II) fibrosis (relative to control and comparison group) may be due to persistent inflammation in the liver parenchyma and an increasing imbalance between the processes of its damage and reparative capabilities. Whereas the decrease in their number at the terminal station fibrosis may indicate an increasing decompensation and depletion of the regenerative potential of the organism in the final stages of the degenerative process.Conclusions. In general, the obtained data demonstrate new aspects of the immune regulation of the processes of fibrogenesis in chronic alcoholism.